HEDGES ALGEBRAS AND PROBLEM FUZZY PARTITION FOR QUALITATIVE ATTRIBUTES - Anh, Nguyen Tuan; Son, Trran Thai (Journal of Computer Science and Cybernetics, 2017)
The pager refers to the construction of sets of the membership functions (MFs), which partition quantitative attributes in database into optimal fuzzy domains for extracting fuzzy association rules in the direction of hedge algebras approach. Some advantages of this method is demonstrated through the analysis of experiments on one set of standard data.Keywords. Data mining; fuzzy association rules; genetic algorithms; membership functions; Hedgealgebras